Nonsteroid drug selectivities for cyclo-oxygenase-1 rather than cyclo-oxygenase-2 are associated with human gastrointestinal toxicity: A full in vitro analysis - Warner, Timothy D. (The National Academy of Sciences, 1999)
The beneficial actions of nonsteroid anti-inflammatory drugs (NSAID) can be associated with inhibition of cyclo-oxygenase (COX)-2 whereas their harmful side effects are associated with inhibition of COX-1. Here we report data from two related assay systems, the human whole blood assay and a modified human whole blood assay (using human A549 cells as a source of COX-2). This assay we refer to as the William Harvey Modified Assay. Our aim was to make meaningful comparisons of both classical NSAIDs and newer COX-2-selective compounds. These comparisons of the actions of >40 NSAIDs and novel COX-2-selective agents, including celecoxib, rofecoxib and diisopropyl fluorophosphate, demonstrate a distribution of compound selectivities toward COX-1 that aligns with the risk of serious gastrointestinal complications. In conclusion, this full in vitro analysis of COX-1/2 selectivities in human tissues clearly supports the theory that inhibition of COX-1 underlies the gastrointestinal toxicity of NSAIDs in man.